The importance of child care in primary health care, and its correlation with autism spectrum disorder: an integrative review (Research, Society and Development, 2022)
Historically, childcare is an intrinsic activity of pediatrics, focusing on child well-being, aiming at an adequate neuropsychomotor development. Initially, childcare was described as a means of improving children's hygienic and physiological conditions, with pediatricians primarily responsible for carrying out this action. From there, there was the emergence of protocols to guide mothers on the care and feeding of their children. In this sense, the new childcare, a science that encompasses knowledge from physiology and sociology, promotes its care from the child to its family, alerting mainly to the prevention of chronic diseases in adults that start in utero and in the first two years of life. child, especially related to behavioral disorders. In this way, this work aims to raise new perspectives on childcare in primary health care and highlight the pediatrician's action in helping to identify ASD (Autism Spectrum Disorder), one of the most prevalent behavioral disorders today. The importance of this review will contribute to the update on protocols of care in primary care, from the 1st to the 24th month of life of newborns, where it will help professionals from the Family Health Strategies on childcare notions, facilitating the development of the bond between the team of health and the newborn's family. Therefore, knowing and establishing the proper practice of childcare becomes essential to address increasingly incident issues, such as behavioral disorders and, consequently, to improve the quality of life of future young people and adults.